Constitutive modeling of geomaterials principles and applications - Nakai, Teruo (CRC Press, 2013)
For three-dimensional constitutive modeling in this book, attention is paid to the so-called spatially mobilized plane (SMP) on which the shear-normal stress ratio is the quadratic mean of maximum shear-normal stress ratios between two respective principal stresses